Gender Food Mapping for Boiled Sweetpotato in Mozambique. RTB Technical Report - Mayanja, S.; Tinyiro, E.S.; Kisakye, S.; Anena, B.; Asasira, M.; Abdul, N.; Mulwa, C.K.; Kawarazuka, Nozomi; Andrade, M.I. (International Potato Center, 2021)
Sweetpotato breeders have strived to breed varieties that address productivity challenges that farmers face in SSA. However, adoption rates for the new varieties are usually low. This has been attributed to the fact that such varieties rarely meet the gendered preferences of the end users in terms of preferred traits and characteristics. This study sought to identify key preferred traits and characteristics by women and men farmers in Manhica and Marracuenne districts, Mozambique. Specifically, the study mapped the livelihood characteristics of the respondents by sex and region in relation to preferred sweetpotato varieties at three levels: the raw root, during processing and the boiled root. Findings show that though sweetpotato was cultivated by all three identified wealth groups, it was of greater importance to the poor and reasonably well-off wealth categories. The moderately well-off category grew the crop mostly for sale, while the poor category produced it for mostly for food. Sweetpotato plots were jointly managed in most households but with demarcated production activities. Sweetpotato was the most important crop for women in Manhiça and for men in Marracuene; while men in Manhiça and women in Marracuene ranked it second. Variety preference: The most preferred variety was N’santimuni and this cut across gender, wealth category and region. In though, one men FGD highlighted that women mostly preferred local varieties such as N’santimuni, Cidinha and Mulumuzani. Likewise, the women FGD in the same location mentioned Bobole, Chihav, Isaura, Manhiça, Melinda and Jane as men’s preferred varieties. In Marracuene, there were no differences for varietal preferences amongst women. There were minimal variations in in the varieties grown given the seed sharing practices across the board. Access to new sweetpotato varieties: New sweetpotato varieties were receive through extension services and many respondents indicated that they were growing them. However, in some instances, “farmer to farmer sharing strategy” was reportedly being adopted in order to spread these varieties in the community. In Marracuene for example women respondents reported having received OFSP varieties such as Martinha, Victória, Cidinha and Manhiça as well as some purple-fleshed varieties. In Manhiça, both men and women mentioned that women made the decisions on adoption and production of new sweetpotato potato varieties. New Variety liking and ranking: In Manhiça for example, men liked the new varieties because of good taste, high yields and in rich in Vitamins; in descending order. Women ranked their preferences as high yields, good taste and market preferred. Importantly, women respondents were variety specific when mentioning their preferences: for example, Ininda had a good taste (roots and leaves), Esther presented roots with good dry matter content like cooked eggs, Irene had vitamins, high yield and good taste, Amélia high yield and good taste (roots and leaves) while Melinda was a high yielding with good taste (roots and leaves). In Marracuene, men preferred characteristics were good taste, rich in vitamins and good for processing. Women ranked good taste, dry matter and rich in vitamins as their most preferred characteristics. High yields featured only in Manhiça; possibly because of the district’s greater marketing focus for sweetpotato. Good sweetpotato characteristics: Which farmers considered when selecting a variety to grow included agronomic traits such as early maturity, high yields and resistant to weevils; postharvest such as high dry matter, no cracks on peel and market preferred; processing, physio-chemical (vitamin rich) and sensory characteristics (good taste, high dry matter). In Manhiça, men prioritized market preferred, dry matter and vitamin rich, while women prioritized dry matter, high yields and market preferred. Men in Marracuene prioritized good taste, good to process and drought tolerance, while women ranked market preferred, high yield and good taste. *Market preference was explained to mean: a good root which was described as beautiful (having a smooth skin and not weevil damage), reasonable size (medium between one and two fists), tasty, easy to cook, having many on farm buyers, and short time spent to sell it off in the market. Varieties with the preferred characteristics: Included N’satimuni, Bowole for men and women in Manhiça, while women in Marracuene selected N’satimuni; Bowole and OFSP tying in second place. For Marracuene men N’satimuni came first followed by OFSP and Lilas in second place. Effect of preferred characteristics on women’s labour, decision making and income control: Men perceived that the preferred characteristics increased market preference, and thus had a positive impact on women’s labour as they were motivated to work harder and earn more income. The early maturing varieties were said to be good for women, as they provided food at a time when stocks were running low, but increased their labour burden. Women perceived that most of the preferred characteristics led to increased labour load, since they were responsible for sweetpotato production. Nonetheless, this was perceived positively given the income anticipated from increased sales of quality roots. The tradeoff for labour was less time for household chores which were relegated to children; and hire of casual labourers were resources were available. With regards to decision making, it was unanimously agreed that women were in charge of production and marketing decisions. However, control of income so earned was perceived to be a joint decision. What characteristics make a good boiled sweetpotato? When selecting the raw root: Men in Marracuene ranked smooth skin, good size, dry matter and good taste as the most important characteristics, while for women good size, smooth skin and no damages were selected. In Manhica, women selected dry matter, not rotten and good taste, while for men it was smooth skin, good size and dry matter. At processing: for men, important characteristics at this stage were good taste, smooth skin and dry matter while for women it was no fibers, good, no damages and smooth skin Ready to eat: boiled sweetpotato was consumed with tea and salad, or mashed and mixed with groundnuts (Xiguinha). Important characteristics that made a good boiled sweetpotato for men were easy to peel, with good dry matter, goo aroma and beautiful smooth skin. Women ranked good dry matter, low fibre content, smooth skin and not rotten as the most important characteristics. In summary, though there were differences in the ranking of preferred characteristics and varieties for men and women, and across regions; these differences would not create difficulties in developing a new product profile. Breeders should nonetheless be cognizant of the characteristics that make the local variety N’santimuni stand out for women when breeding for a replacement candidate, as they in ranking; while some are different from men’s. Whereas absence of fiber is important for women for example, this does not feature in men’s preferred final product characteristics nor at processing. Given women’s position in the sweetpotato value chain, prioritizing their preferred characteristics in the product profile could lead to higher adoption of new varieties. For CIP, it is gratifying that farmers in Mozambique are increasingly accepting the OFSP varieties given the high ranking amongst preferred varieties. Again, good characteristics mentioned by women for the various OFSP varieties need to be capitalized on for future OFSP product profiles.